2016
DOI: 10.1186/s40852-016-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

What kind of innovations do we need to secure our future?

Abstract: The question of what kind of innovations can secure our future is in this paper put in perspective with the unknown risks which innovations may imply. Innovations sometimes turn out to cause severe negative externalities after they have successfully passed the market test. In such cases, the social costs that are revealed only later may result in substantial welfare losses. Obviously, innovations of this kind are the opposite of what is needed. Can the knowledge flows related to innovation processes be strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…It is considered that the new opportunity for marketability can be drawn from environmental destruction resulting from the production process in a firm. Sustainability-oriented individuals then produce products that can take the opportunity without undermining the environment [15,16]. Environmental degradation deriving from market imperfection brings entrepreneurial opportunities, and entrepreneurs discover and pursue these opportunities.…”
Section: Sustainability Orientation and Opportunity Recognitionmentioning
confidence: 99%
“…It is considered that the new opportunity for marketability can be drawn from environmental destruction resulting from the production process in a firm. Sustainability-oriented individuals then produce products that can take the opportunity without undermining the environment [15,16]. Environmental degradation deriving from market imperfection brings entrepreneurial opportunities, and entrepreneurs discover and pursue these opportunities.…”
Section: Sustainability Orientation and Opportunity Recognitionmentioning
confidence: 99%
“…Opportunities for interactions are crucial because when the supplier and users interact without boundaries, their respective information and needs generate a valid flow and can enhance the outcomes. For this reason, offering efficient medias (or channels) for gaining specific knowledge can be defined as one of the characteristics of open innovation [47]. In the case study, the working group selectively used both non-face-to-face media for communication, such as email and SNS, and face-to-face media for communication such as group meetings and workshops, depending on the needs.…”
Section: The Effect Of Diversified Media On Enhancing Citizen Particimentioning
confidence: 99%
“…Rather, innovation is a long time cumulative process of a great number of organizational decision-making process, ranging from the phase of generation of a new idea to its implementation phase. As I reviewed, knowledge is key component to innovation; knowledge flows related to innovative activities are a core component of the first major implementations dealing with the details and specificities of how innovations are being created and how the innovation process can best be organized (Witt, 2016). Henderson and Clark (1990) suggested that, concerning architectural innovation and knowledge, architectural innovation destroys the usefulness of a firm's architectural knowledge but preserves the usefulness of its knowledge about the product's components.…”
Section: Architecture Knowledgementioning
confidence: 99%